158 Is it cost effective to use a plugged LV port?. (9th June 2011) - Jones, M A; Betts, T R; Rajappan, K; Bashir, Y; Wong, K C K; Qureshi, N
Abstract : Background: Many patients receiving ICD implants do not meet criteria for CRT therapy, yet are often felt likely to benefit from CRT in the future. The reasons for this include less severe NYHA class of HF symptoms at the time of implant, narrow QRS, and (progressive) atrio-ventricular conduction delay. Management options include only implanting DDD / VVI devices, and then upgrading to CRT if required; implanting CRT-D devices but without an LV lead, with the LV port "plugged", such that if an upgrade were to become necessary, only a new LV lead (and implant kit) would be required; and finally, implanting CRT-D devices with LV leads in all patients in the first instance, as has been suggested by the recent Madit-CRT and RAFT studies. It is not clear which of these strategies is superior in terms of the cost-benefit ratio. Purpose: This study analyses a retrospective cohort of patients who received CRT-D devices but without LV leads, to examine the cost implications of this approach, and to compare this cost to that of merely implanting a DDD device, or implanting a full CRT-D system initially. Method: A retrospective analysis of all patients receiving CRT-ICDs with plugged LV ports between September 2004 and June 2009 at our institution. Patient characteristics, indication for a plugged LV port, subsequent addition of a LV lead and reasons for doing so were taken from patient records. The total cost (surgery and hardware) was compared with the estimated cost of initially implanting single or dual chamber ICDs and upgrading the entire system, and to the cost of implanting full CRT-D systems up front. Results: 35 patients (27 male) were identified. Mean (SD) age was 67±8 years. 26 had ischaemic heart disease and 9 non-ischaemic dilated cardiomyopathy. All had LV EF<30%. Indications for a plugged LV port were LBBB and NYHA class I or II symptoms in 29 and NYHA class I or II with a narrow QRS but a high chance of becoming pacemaker dependent in 6. During a mean (SD) FU of 40 ±16 months, 6 (17%) patients had an LV lead added, all for the development of NYHA III symptoms, at 10, 11, 15, 17, 17 and 21 months respectively. Total cost at end of FU period was £ 654 000. If all patients had initially been implanted with VVI or DDD ICDs and 6 new CRT systems implanted, the estimated cost would have been £ 598 000. If all patients had received full CRT-D the cost would have been £ 665 000. Taking into account the time to develop symptoms, it is predicted that an upgrade rate of 26%–31% would be required before using a plugged LV port becomes cost-effective. Furthermore, full CRT-D system implantation is even less cost effective. Conclusion: In this series of ICD patients with potential CRT indications but minimal heart failure symptoms, only a small proportion subsequently required biventricular pacing. Using a CRT-ICD with a plugged LV port is not a cost effective strategy (Abstract 158 figure 1 ).